SECURITY POLICY OF CZECH REPUBLIC IN THE AMERICAN-RUSSIAN RELATIONS - Криворучко, Н. В. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Idea, 2019)
The security policy of small states usually formed under the influence regional players and the main geopolitical partners. The objective of the article is to define the main areas the clash of interests of the United States and the Czech Republic. On the example of modernization of the Czech nuclear power plant «Temelin» traced back the limits US-Russian confrontation, and outlines the feasibility of Czech security policy as a small state. The article analyzes the ways of of transformation foreign and security policy of the Czech Republic as small state to state, capable to shape the principles of security policy with regional leaders states by the of Central and Eastern Europe.